Computerised attention training for children with intellectual and developmental disabilities: a randomised controlled trial. (23rd August 2016) - Kirk, Hannah E.; Gray, Kylie M.; Ellis, Kirsten; Taffe, John; Cornish, Kim M.
Abstract : Background: Children with intellectual and developmental disabilities (IDD) experience heightened attention difficulties which have been linked to poorer cognitive, academic and social outcomes. Although, increasing research has focused on the potential of computerised cognitive training in reducing attention problems, limited studies have assessed whether this intervention could be utilised for those with IDD. This study aimed to assess the efficacy of a computerised attention training programme in children with IDD. Methods: In a double‐blind randomised controlled trial, children ( n = 76; IQ < 75) aged 4–11 years were assigned to an adaptive attention training condition or a nonadaptive control condition. Both conditions were completed at home over a 5‐week period and consisted of 25 sessions, each of 20‐min duration. Outcome measures (baseline, posttraining and 3‐month follow‐up) assessed core attention skills (selective attention, sustained attention and attentional control) and inattentive/hyperactive behaviour. Results: Children in the attention training condition showed greater improvement in selective attention performance compared to children in the control condition (SMD = 0.24, 95% CI 0.02, 0.45). These improvements were maintained 3 months after training had ceased (SMD = 0.26, 95% CI 0.04, 0.48). The attention training programme was not effective in promoting improvements in sustained attention, attentional control or inattentive/hyperactive behaviours. Conclusions: The findings suggest that attention training may enhance some aspects of attention (selective attention) in children with IDD, but the small to medium effect sizes indicate that further refinement of the training programme is needed to promote larger, more global improvements.